Leptosphaeria maculans effector AvrLm4-7 affects salicylic acid (SA) and ethylene (ET) signalling and hydrogen peroxide (H2 O2 ) accumulation in Brassica napus - Nováková, Miroslava; Šašek, Vladimír; Trdá, Lucie; Krutinová, Hana; Mongin, Thomas; Valentová, Olga; Balesdent, Marie-HelEne; Rouxel, Thierry; Burketová, Lenka (Molecular plant pathology, 2016)
To achieve host colonization, successful pathogens need to overcome plant basal defences. For this, (hemi)biotrophic pathogens secrete effectors that interfere with a range of physiological processes of the host plant. AvrLm4-7 is one of the cloned effectors from the hemibiotrophic fungus Leptosphaeria maculans 'brassicaceae' infecting mainly oilseed rape (Brassica napus). Although its mode of action is still unknown, AvrLm4-7 is strongly involved in L. maculans virulence. Here, we investigated the effect of AvrLm4-7 on plant defence responses in a susceptible cultivar of B. napus. Using two isogenic L. maculans isolates differing in the presence of a functional AvrLm4-7 allele [absence ('a4a7') and presence ('A4A7') of the allele], the plant hormone concentrations, defence-related gene transcription and reactive oxygen species (ROS) accumulation were analysed in infected B. napus cotyledons. Various components of the plant immune system were affected. Infection with the 'A4A7' isolate caused suppression of salicylic acid- and ethylene-dependent signalling, the pathways regulating an effective defence against L. maculans infection. Furthermore, ROS accumulation was decreased in cotyledons infected with the 'A4A7' isolate. Treatment with an antioxidant agent, ascorbic acid, increased the aggressiveness of the 'a4a7' L. maculans isolate, but not that of the 'A4A7' isolate. Together, our results suggest that the increased aggressiveness of the 'A4A7' L. maculans isolate could be caused by defects in ROS-dependent defence and/or linked to suppressed SA and ET signalling. This is the first study to provide insights into the manipulation of B. napus defence responses by an effector of L. maculans.
Keywords: Salicylic Acid; Chromatography, Liquid; antioxidancia; Host-Pathogen Interactions; effector; Abscisic Acid; AvrLm4-7; salicylic acid; kyselina askorbová; ROS; signální transdukce; Oxylipins; regulátory růstu rostlin; Fungal Proteins; oxylipiny; kotyledon; peroxid vodíku; Mass Spectrometry; polymerázová řetězová reakce s reverzní transkripcí; Ascorbic Acid; Hydrogen Peroxide; chromatografie kapalinová; Signal Transduction; Leptosphaeria; ethylene; Plant Growth Regulators; kyselina salicylová; Antioxidants; interakce hostitele a patogenu; Reverse Transcriptase Polymerase Chain Reaction; Ascomycota; Cyclopentanes; Brassica napus; hmotnostní spektrometrie; Alleles; cyklopentany; Cotyledon; Ethylenes; alely; fungální proteiny; kyselina abscisová; ethyleny